2021
DOI: 10.1111/myc.13367
|View full text |Cite
|
Sign up to set email alerts
|

Predicting a therapeutic cut‐off serum level of itraconazole in recalcitrant tinea corporis and cruris—A prospective trial

Abstract: The alarming increase of resistant dermatophytic infections in India over the past few years has been a major concern to the medical community. [1][2][3][4] Antifungal resistant dermatophytoses is now spreading globally 5-7 because of widespread travel and migration, and has recently been described in Europe as well. 8,9 The likely factors contributing to this disconcerting phenomenon include, but are not

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
1
22
0
3
Order By: Relevance
“…However, oral formulations of ITC have erratic absorption patterns leading to wide fluctuations in its serum concentrations. Although, monitoring of serum levels of ITC as in systemic mycoses is important for effective treatment outcome [ 41 , 42 ]. However, the high cost burden associated with regular therapeutic drug monitoring for this extremely prevalent infection, especially in lower-middle countries, is not practical.…”
Section: Multidrug-resistant T Indotine...mentioning
confidence: 99%
“…However, oral formulations of ITC have erratic absorption patterns leading to wide fluctuations in its serum concentrations. Although, monitoring of serum levels of ITC as in systemic mycoses is important for effective treatment outcome [ 41 , 42 ]. However, the high cost burden associated with regular therapeutic drug monitoring for this extremely prevalent infection, especially in lower-middle countries, is not practical.…”
Section: Multidrug-resistant T Indotine...mentioning
confidence: 99%
“… 21 26 However, Khurana et al indicated a cut-off value of serum concentration of 200 ng/mL in dermatophytosis. 27 Although toxicity levels of plasma ITZ are challenging to assess, some studies indicated that C trough levels between 2,000 and 5000 ng/mL are suggestive of increased side-effect profiles. 28 , 29 In present study, C trough levels from day 1 onwards were never above 2000 ng/mL in any of the groups, indicating safety even at high OD dosing.…”
Section: Discussionmentioning
confidence: 99%
“…This observed increase in frequency and severity has been attributed to many factors including the widespread use of high-potency steroids in topical formulations and misuse of antifungal agents. Host-related factors, abnormal drug pharmacokinetics (PK) [ 7 , 8 ], and differences in bioavailability among many itraconazole formulations available in India [ 9 ], have been considered among the factors for treatment failures. To date, there is no clear evidence that supports these observations.…”
Section: Introductionmentioning
confidence: 99%